2013
DOI: 10.1016/j.ccr.2013.07.012
|View full text |Cite|
|
Sign up to set email alerts
|

A Kinase-Independent Function of CDK6 Links the Cell Cycle to Tumor Angiogenesis

Abstract: SummaryIn contrast to its close homolog CDK4, the cell cycle kinase CDK6 is expressed at high levels in lymphoid malignancies. In a model for p185BCR-ABL+ B-acute lymphoid leukemia, we show that CDK6 is part of a transcription complex that induces the expression of the tumor suppressor p16INK4a and the pro-angiogenic factor VEGF-A. This function is independent of CDK6’s kinase activity. High CDK6 expression thus suppresses proliferation by upregulating p16INK4a, providing an internal safeguard. However, in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
201
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 255 publications
(205 citation statements)
references
References 72 publications
4
201
0
Order By: Relevance
“…The reason may be that CDK6 was targeted by miR-3928. Interestingly, recent study showed that CDK6 linked the cell cycle to tumor angiogenesis [35]. Angiogenesis is a key step of tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…The reason may be that CDK6 was targeted by miR-3928. Interestingly, recent study showed that CDK6 linked the cell cycle to tumor angiogenesis [35]. Angiogenesis is a key step of tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…This repression affected downstream cancer-related effectors, including CDK6 (Zhou et al, 2014). Although the role of CDK6 in the initiation and development of tumors has been well-characterized (Kollmann et al, 2013), the underlying mechanism(s) responsible for the regulation of CDK6 by NFIB remain unclear. Interactions between CDK6 and CDK4 have been described as well (Kollmann et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of CDK6 in the initiation and development of tumors has been well-characterized (Kollmann et al, 2013), the underlying mechanism(s) responsible for the regulation of CDK6 by NFIB remain unclear. Interactions between CDK6 and CDK4 have been described as well (Kollmann et al, 2013). Thus, an important question is whether CDK4 is also regulated by NFIB.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, binding of CDK6 to the p16 INK4A promoter crucially depends on the presence of STAT3 [39], showing that CDK6 can utilize different transcription factor complexes to mediate its association with distinct chromatin regions. In agreement with the dynamic association of CDK6 with different transcription factor complexes, a previous study revealed the testosterone-inducible interaction of CDK6 with the androgen receptor, a nuclear hormone receptor that regulates transcription of the prostate-specific antigen (PSA) gene [40].…”
Section: Stat Transcription Factorsmentioning
confidence: 94%
“…Besides NF-kB p65, a further candidate transcription factor is PAX4 (paired box 4), whose consensus DNA-binding motif is associated with a fraction of CDK6 peaks. However, CDK6 does not only associate with p65 because in BCR-ABL (breakpoint cluster region-Abelson oncogene homolog)-transformed B-acute lymphoid leukemia cells the kinase interacts also with STAT3 and the AP-1 transcription factor subunit JUN (Jun protooncogene) [39], as summarized in Figure 2B.…”
Section: Stat Transcription Factorsmentioning
confidence: 99%